Enhancing Pregnant Women’s Knowledge Through the Implementation of the Gerigi (Maternal Dental Care Movement) Program at Wolowa Community Health Center, Buton Regency - Syahrir Ramadhan Bukide (Sean Institute, 2025)
Maternal oral health is a critical yet often overlooked component of prenatal care, despite its significant association with adverse pregnancy outcomes such as preterm birth and Low Birth Weight (LBW). At the Wolowa Community Health Center (Puskesmas) in Buton Regency, a lack of awareness among pregnant women regarding the importance of dental care has led to low utilization of dental clinic services. This study aimed to evaluate the effectiveness of the